Spatial variability of the dose rate from 137Cs fallout in settlements in Russia and Belarus more than two decades after the Chernobyl accident. (November 2015) - Bernhardsson, C.; Rääf, C.L.; Mattsson, S.
Abstract: Radionuclides from the 1986 Chernobyl accident were released and dispersed during a limited period of time, but under widely varying weather conditions. As a result, there was a high geographical variation in the deposited radioactive fallout per unit area over Europe, depending on the released composition of fission products and the weather during the 10 days of releases. If the plume from Chernobyl coincided with rain, then the radionuclides were unevenly distributed on the ground. However, large variations in the initial fallout also occurred locally or even on a meter scale. Over the ensuing years the initial deposition may have been altered further by different weathering processes or human activities such as agriculture, gardening, and decontamination measures. Using measurements taken more than two decades after the accident, we report on the inhomogeneous distribution of the ground deposition of the fission product 137 Cs and its influence on the dose rate 1 m above ground, on both large and small scales (10 ths of km 2 – 1 m 2 ), in the Gomel–Bryansk area close to the border between Belarus and Russia. The dose rate from the deposition was observed to vary by one order of magnitude depending on the size of the area considered, whether human processes were applied to the surface or not, and on location specific properties ( e . g . radionuclide migration in soil). Highlights: We have surveyed the variability in dose rate after the Chernobyl accident. A high dose rate variability is observed on both large- and small scales. The intra-site variability is generally smaller than the inter-site variability. The variability tend to reduce by human influence on the ground.